2019
DOI: 10.1088/1402-4896/ab34bb
|View full text |Cite
|
Sign up to set email alerts
|

On model of hybrid Casson nanomaterial considering endoscopy in a curved annulas: a comparative study

Abstract: This paper explores the complex rheological non-Newtonian fluid flow model in a two-dimensional annulus of curved nature, which is comprise of two cylinders in which inward cylinder is viewed as inflexible while outer cylinder is flexible. In modeling of Casson fluid flow, constitutive equation under certain approximations are considered in most comprehensive way to represent it effectively as an enhancement of Newtonian fluid model. As nanoparticles are potential vehicle for drug transport in biomedical study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Irshad et al 13 had mathematically modelled the heat transfer for peristaltic flow inside a curved channel with endoscopic applications. Shahzadi et al 14 had disclosed the mathematical analysis of heat transfer inside a curved annulus with endoscopic applications. Entropy generation is also important in many of the endoscopic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Irshad et al 13 had mathematically modelled the heat transfer for peristaltic flow inside a curved channel with endoscopic applications. Shahzadi et al 14 had disclosed the mathematical analysis of heat transfer inside a curved annulus with endoscopic applications. Entropy generation is also important in many of the endoscopic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid nanofluids are widely utilized in nanotechnological applications 1 . Shahzadi and Ijaz 2 performed a comparative study on the flow of a Casson hybrid nanofluid over a curved annulus. The mixed convective hybrid nanofluid stream past a permeable medium was inspected by Waini et al 3 Thriveni and Mahanthesh 4 deliberated the buoyancy‐driven flow of a hybrid nanoliquid in an annulus with radiation and magnetic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Ijaz and Nadeem 10 theoretically investigated the heat transfer characteristics in a blood flow through atherosclerotic artery under the impact of nano fluid they found blood containing nano fluid mediation in blood is helpful to minimize the hemodynamic impact. A theoretical model of Casson hybrid nano fluid in a curved annulus was proposed by Shahzadi and Ijaz 11 . They observed that stress formation in a curve for non-Newtonian parameter is higher than that of viscus case.…”
Section: Introductionmentioning
confidence: 99%